Characterization of micellar systems produced by new amphiphilic conjugates of poly(ethylene glycol). (November 2014) - Pignatello, R.; Pantò, V.; Basile, L.; Leonardi, A.; Guarino, C.; La Rosa, C.
Abstract This study proposes polymeric micelles produced using new amphiphilic conjugates between amino- or carboxy-mPEG2000 and three different α-lipoamino acids (PEG-LAA). The characterization of these colloidal systems showed CMC values, in the order of 10−5 M, that are interesting in the view of an in vivo administration. The PEG-LAA micelles also showed a good stability at 37 °C and upon dilution in aqueous media. Using a colored probe as a model lipophilic compound, the loading efficiency and in vitro release profile were also outlined.